2017
DOI: 10.1021/acs.energyfuels.7b03002
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Transfer Performance for CO2 Absorption by 2-(2-Aminoethylamino)ethanol Solution in a Rotating Packed Bed

Abstract: The emission of CO 2 is leading to serious global climate change, which has attracted increasing attention. In this work, a rotating packed bed (RPB) was employed as a highly effective reactor to intensify the CO 2 absorption in an alkanolamine solution that mainly contained 2-(2-aminoethylamino)ethanol (AEEA). The effects of important operating conditions, such as high gravity level, amine solvent concentration, gas/liquid flow ratio, CO 2 inlet concentration, absorption temperature, and CO 2 loading in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Ma and Chen reported that the MMEA solutions exhibited a higher removal efficiency than MEA because MMEA reacts faster with CO 2 than MEA . Wu et al performed absorption of CO 2 in an RPB using AEEA solutions and showed that the mass transfer coefficient was an order of magnitude higher than that in a packed column . Sheng et al reported that the aqueous solution of DETA was an effective absorbent for CO 2 capture in an RPB .…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Ma and Chen reported that the MMEA solutions exhibited a higher removal efficiency than MEA because MMEA reacts faster with CO 2 than MEA . Wu et al performed absorption of CO 2 in an RPB using AEEA solutions and showed that the mass transfer coefficient was an order of magnitude higher than that in a packed column . Sheng et al reported that the aqueous solution of DETA was an effective absorbent for CO 2 capture in an RPB .…”
Section: Introductionmentioning
confidence: 89%
“…Many investigations have studied the capture of CO 2 in an RPB using various alkanolamine solutions, including monoethanolamine (MEA), 2‐amino‐2‐methyl‐1‐propanol (AMP), methyl‐diethanolamine (MDEA), 2‐(2‐aminoethylamino)ethanol (AEEA), diethanolamine (DEA), diethylenetriamine (DETA), 2‐methyl‐amino‐ethanol (MMEA) and piperazine (PZ) . Alkanolamines that react rapidly with CO 2 , such as MEA, MMEA, AEEA, DETA, and PZ are favored because of the short residence time in an RPB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ANN, a typical sort of deep learning, is popularly and widely used in chemical engineering. , When applying an ANN, there is no need to consider the inherent mechanism of processes or phenomena. Some highly nonlinear and complex problems can be better handled . The ANN model is a black box operation with multi-input and multi-output data by using different structures and nonlinear basis functions .…”
Section: Methodsmentioning
confidence: 99%